Preparation of Polycrystalline Silicon from Rice Husk by Thermal Decomposition and Aluminothermic Reduction - Ahmad Nuruddin; Brian Yuliarto; Adhitya Gandaryus Saputro; Badruzaman Badruzaman; Aditianto Ramelan (Universitas Jenderal Soedirman, 2020)
Polycrystalline silicon was extracted from rice husk by thermal decomposition and aluminothermic methods. Rice husk was thermally decomposed under various heat treatments and acid purifications. High purity silica of 99.81% was obtained by subsequent rice husk washing, pressure cooking in mixed chloride acid peroxide solution, and burning at 500oC for one hour. Aluminothermic reduction of silica was conducted at various calcination temperatures. It is found that 78.6% of silica was converted to silicon for calcination temperature of 800oC. Leaching the reduction product with strong hydrochloric and hydrofluoric acids produced silicon polycrystalline with a purity of 99.91%.